![image](https://tex.z-dn.net/?f=%20%5Csqrt%5B4%5D%7B%20x%20%2B%201%7D%20%3D%202x%20%2B%202%5C%5C%20%5Csqrt%5B4%5D%7B%20x%20%2B%201%7D%20%3D%202%28x%20%2B%201%29%20%5C%5C%20y%20%3D%20%5Csqrt%5B4%5D%7Bx%20%2B%201%7D%20%5Cgeqslant%200%20%5C%5C%20y%20%3D%202%20%7By%7D%5E%7B4%7D%20%5C%5C%202%20%7By%7D%5E%7B4%7D%20-%20y%20%3D%200%20%5C%5C%20y%282%20%7By%7D%5E%7B3%7D%20-%201%29%20%3D%200%20%5C%5C%20y_1%3D%200%20%3D%20%3E%20%5Csqrt%5B4%5D%7Bx%20%2B%201%7D%20%3D%200%20%5C%5C%3D%20%3E%20x_1%3D%20-%201%20%5C%5C%20%5C%5C%202%20%7By%7D%5E%7B3%7D%20-%201%20%3D%200%20%5C%5C%20%7By%7D%5E%7B3%7D%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%5C%5C%20y_2%3D%20%5Csqrt%5B3%5D%7B%20%5Cfrac%7B1%7D%7B2%7D%20%7D%20%5C%5C%20%5Csqrt%5B4%5D%7Bx%20%2B%201%7D%20%3D%20%5Csqrt%5B3%5D%7B%20%5Cfrac%7B1%7D%7B2%7D%20%7D%20%5C%5C%20x%20%2B%201%20%3D%20%5Cfrac%7B1%7D%7B2%7D%20%5Csqrt%5B3%5D%7B%20%5Cfrac%7B1%7D%7B2%7D%20%7D%20%5C%5C%20x_2%3D%20%5Cfrac%7B1%7D%7B2%7D%20%5Csqrt%5B3%5D%7B%20%5Cfrac%7B1%7D%7B2%7D%20%7D%20-%201%20%5C%5C%20%5C%5C%20%5C%5C%20x_1%3D%20-%201%5C%5C%20x_2%3D%20%5Cfrac%7B1%7D%7B2%7D%20%5Csqrt%5B3%5D%7B%20%5Cfrac%7B1%7D%7B2%7D%20%7D%20-%201%20%5C%5C%20)
\sqrt[4]{x + 1} = 0 \\= > x_1= - 1 \\ \\ 2 {y}^{3} - 1 = 0 \\ {y}^{3} = \frac{1}{2} \\ y_2= \sqrt[3]{ \frac{1}{2} } \\ \sqrt[4]{x + 1} = \sqrt[3]{ \frac{1}{2} } \\ x + 1 = \frac{1}{2} \sqrt[3]{ \frac{1}{2} } \\ x_2= \frac{1}{2} \sqrt[3]{ \frac{1}{2} } - 1 \\ \\ \\ x_1= - 1\\ x_2= \frac{1}{2} \sqrt[3]{ \frac{1}{2} } - 1 \\ " alt=" \sqrt[4]{ x + 1} = 2x + 2\\ \sqrt[4]{ x + 1} = 2(x + 1) \\ y = \sqrt[4]{x + 1} \geqslant 0 \\ y = 2 {y}^{4} \\ 2 {y}^{4} - y = 0 \\ y(2 {y}^{3} - 1) = 0 \\ y_1= 0 = > \sqrt[4]{x + 1} = 0 \\= > x_1= - 1 \\ \\ 2 {y}^{3} - 1 = 0 \\ {y}^{3} = \frac{1}{2} \\ y_2= \sqrt[3]{ \frac{1}{2} } \\ \sqrt[4]{x + 1} = \sqrt[3]{ \frac{1}{2} } \\ x + 1 = \frac{1}{2} \sqrt[3]{ \frac{1}{2} } \\ x_2= \frac{1}{2} \sqrt[3]{ \frac{1}{2} } - 1 \\ \\ \\ x_1= - 1\\ x_2= \frac{1}{2} \sqrt[3]{ \frac{1}{2} } - 1 \\ " align="absmiddle" class="latex-formula">